A conventional immune regulator mitochondrial antiviral signaling protein blocks hepatic steatosis by maintaining mitochondrial homeostasis. Issue 2 (12th December 2021) - Fu, Jiajun; Hu, Fengjiao; Ma, Tengfei; Zhao, Wen‐Jie; Tian, Han; Zhang, Yan; Hu, Manli; Zhou, Junjie; Zhang, Yanfang; Jian, Chongshu; Ji, Yan‐Xiao; Zhang, Xiao‐Jing; et al.
Abstract : Background and Aims: Although the prevalence of NAFLD has risen dramatically to 25% of the adult population worldwide, there are as yet no approved pharmacological interventions for the disease because of uncertainty about the underlying molecular mechanisms. It is known that mitochondrial dysfunction is an important factor in the development of NAFLD. Mitochondrial antiviral signaling protein (MAVS) is a critical signaling adaptor for host defenses against viral infection. However, the role of MAVS in mitochondrial metabolism during NAFLD progression remains largely unknown. Approach and Results: Based on expression analysis, we identified a marked down‐regulation of MAVS in hepatocytes during NAFLD progression. By using MAVS global knockout and hepatocyte‐specific MAVS knockout mice, we found that MAVS is protective against diet‐induced NAFLD. MAVS deficiency induces extensive mitochondrial dysfunction during NAFLD pathogenesis, which was confirmed as impaired mitochondrial respiratory capacity and membrane potential. Metabolomics data also showed the extensive metabolic disorders after MAVS deletion. Mechanistically, MAVS interacts with the N‐terminal stretch of voltage‐dependent anion channel 2 (VDAC2), which is required for the ability of MAVS to influence mitochondrial function and hepatic steatosis. Conclusions: In hepatocytes, MAVS plays an important role in protecting against NAFLD by helping to regulate healthy mitochondrial function. These findings provide insights regarding the metabolic importance of conventional immune regulators and support the possibility that targeting MAVS may represent an avenue for treating NAFLD.